2018
DOI: 10.1155/2018/2178469
|View full text |Cite
|
Sign up to set email alerts
|

Age Is Not a Limiting Factor in Interventional Radiotherapy (Brachytherapy) for Patients with Localized Cancer

Abstract: This review examines the role of interventional radiotherapy (IRT otherwise known as brachytherapy) in cancer treatment for elderly patients. Despite their advanced age and associated comorbidities, elderly patients should receive definitive cancer therapies, including surgery and radiotherapy (RT). In fact, RT becomes first-line option for patients who are not eligible for surgery (due to comorbidities, anticoagulant drugs, and risk of disfigurement) or those who refuse it. It emerged from this review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 133 publications
(110 reference statements)
0
38
0
Order By: Relevance
“…A review article on brachytherapy in nonmelanoma skin cancer of the eyelid concluded that brachytherapy provides high clinical efficacy (median local control rate 95.2%) and good functional-cosmetic outcome (median 100%) [34]. In addition, especially in old and frail patients, brachytherapy is a safe treatment modality [35]. …”
Section: Discussionmentioning
confidence: 99%
“…A review article on brachytherapy in nonmelanoma skin cancer of the eyelid concluded that brachytherapy provides high clinical efficacy (median local control rate 95.2%) and good functional-cosmetic outcome (median 100%) [34]. In addition, especially in old and frail patients, brachytherapy is a safe treatment modality [35]. …”
Section: Discussionmentioning
confidence: 99%
“…APBI allows the delivery of higher radiation doses in the area of the tumor bed whilst reducing the dose received by normal breast tissue and adjacent organs at risk. Shorter treatment times and acceptable acute toxicity rates can improve patient quality of life whilst also reducing the total cost of treatment (10)(11)(12)(13)(14). Linear accelerators are the most commonly used devices for delivering external beam radiation to patients.…”
Section: Radiotherapy In Breast Cancer Treatmentmentioning
confidence: 99%
“…Brachytherapy (BT, interventional radiotherapy -IRT) is a kind of radiation therapy, in which the radioactive source is placed nearby or even inside the cancer itself; BT may be used alone or in combination with other thera-peutic strategies such as external beam radiation therapy, surgery, or chemotherapy. It may represent a valid alternative to surgery in some circumstances [1] or a necessary complementary step to surgery in other situations [2], therefore it plays a pivotal role in several anatomical areas, or in specific patients who may benefit from the method in a balance between risks and benefits, such as elderly or frail patients [3,4].…”
Section: Purposementioning
confidence: 99%